2012
DOI: 10.1371/annotation/8690bb36-3c5d-48a6-b3be-39a2b50896e1
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Impaired Transcriptional Activity of Nrf2 in Age-Related Myocardial Oxidative Stress Is Reversible by Moderate Exercise Training

Abstract: Aging promotes accumulation of reactive oxygen/nitrogen species (ROS/RNS) in cardiomyocytes, which leads to contractile dysfunction and cardiac abnormalities. These changes may contribute to increased cardiovascular disease in the elderly. Inducible antioxidant pathways are regulated by nuclear erythroid 2 p45-related factor 2 (Nrf2) through antioxidant response cis-elements (AREs) and are impaired in the aging heart. Whereas acute exercise stress (AES) activates Nrf2 signaling and promotes myocardial antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Numerous studies have reported that Nrf2 is a master transcriptional factor of antioxidant genes, regulating antioxidant gene expression through their antioxidant response element ARE binding sites (Gounder et al, 2012; Muthusamy et al, 2012; Pall and Levine, 2015). We and others have reported that aging decreases Nrf2 (Safdar et al, 2010; Gounder et al, 2012; Done et al, 2016) and thus to determine whether chronic endurance training exacerbates the age-associated alterations in antioxidant gene expression in the absence of Nrf2, we performed real time PCR analysis for the common Nrf2 target antioxidant gene expression in the aged WT and Nrf2 −/− mouse hearts.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous studies have reported that Nrf2 is a master transcriptional factor of antioxidant genes, regulating antioxidant gene expression through their antioxidant response element ARE binding sites (Gounder et al, 2012; Muthusamy et al, 2012; Pall and Levine, 2015). We and others have reported that aging decreases Nrf2 (Safdar et al, 2010; Gounder et al, 2012; Done et al, 2016) and thus to determine whether chronic endurance training exacerbates the age-associated alterations in antioxidant gene expression in the absence of Nrf2, we performed real time PCR analysis for the common Nrf2 target antioxidant gene expression in the aged WT and Nrf2 −/− mouse hearts.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have reported that aging decreases Nrf2 (Safdar et al, 2010; Gounder et al, 2012; Done et al, 2016) and thus to determine whether chronic endurance training exacerbates the age-associated alterations in antioxidant gene expression in the absence of Nrf2, we performed real time PCR analysis for the common Nrf2 target antioxidant gene expression in the aged WT and Nrf2 −/− mouse hearts. Under sedentary conditions, Nrf2 deficiency resulted in a significant decrease in the expression of Nqo1, Gclm, Ho-1, Sod1, Gst- α in Nrf2 −/− mice in relation to aged WT mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, in general, an active lifestyle has been related to physiological, metabolic, and transcriptional changes that support the prevention of chronic diseases such as diabetes, as well as preventing or delaying muscle-mass atrophy caused by aging [33]. In another sense, it has been observed that acute exhaustive training dramatically increases the production of free radicals [34]. Vigorous exercise has been demonstrated to occasionally cause sudden cardiac death in sedentary individuals with prior cardiovascular disease, but this is not the case with the habitual practice of moderate exercise [35].…”
Section: Physical Exercise and Redox Responsementioning
confidence: 99%